Comparative analysis of albumin quotient and total CSF protein in immune-mediated neuropathies: a multicenter study on diagnostic implications - Seeliger, Tabea; Gingele, Stefan; Güzeloglu, Yunus Emre; Heitmann, Lena; Lüling, Benjamin; Kohle, Felix; Preßler, Hannah; Stascheit, Frauke; Motte, Jeremias; Fisse, Anna Lena; Grüter, Thomas; Pitarokoili, Kalliopi; et al. (Frontiers in Neurology, 2024)
Introduction: Blood-cerebrospinal fluid (CSF) barrier dysfunction is pivotal for diagnosing immune-mediated neuropathies, especially in spinal nerve root inflammation. Typically, either total CSF protein or the CSF to serum albumin ratio (QAlb) is measured. Total CSF protein measurements have limitations, notably its fixed reference value regardless of age, in contrast to the age-dependent reference for QAlb. Our goal was to evaluate both markers in patients with immune-mediated neuropathies. Methods: In our multicenter research, we collected retrospective CSF data from patients suffering from immune-mediated neuropathies across four German research centers. These parameters were analyzed in relation to their clinical characteristics. Results: Out of 419 samples, 36 (8.6%) displayed a notable variation between total CSF protein and QAlb values. A detailed analysis revealed that patients displaying elevated QAlb but normal total CSF protein levels were significantly younger at disease onset (p=0.01), at the time of diagnosis (p=0.005), and when undergoing lumbar puncture (p=0.001) compared to patients with elevated CSF protein and normal QAlb levels. These effects were especially evident for the subgroup of samples derived by female patients. Discussion: Our work confirms the crucial role of QAlb in diagnosing immune-mediated neuropathies and particularly its efficacy as a marker for evaluating the blood-CSF barrier in patients with an earlier disease onset. Considering the significance of the albumin quotient, its assessment is especially advisable in younger patients of female sex to avoid missing a potential barrier dysfunction that might be falsely negative when using total protein.